Hank's big day the story of a bug - Kuhlman, Evan (Schwartz & Wade Books, 2016)
Hank is a pill bug whose daily routine involves nibbling a dead leaf, climbing up a long stick, avoiding a skateboarder, and playing pretend with his best friend, a human girl named Amelia
Keywords: JUVENILE FICTION / Animals / Insects, Spiders, etc. / bisacsh; JUVENILE FICTION / Nature & the Natural World / General (see also headings under Animals) / bisacsh; JUVENILE FICTION / Social Issues / Self-Esteem & Self-Reliance / bisacsh; Wood lice (Crustaceans); Human-animal relationships; Best friends; Play; JUVENILE FICTION / Animals / Insects, Spiders, etc.; JUVENILE FICTION / Nature & the Natural World / General (see also headings under Animals); JUVENILE FICTION / Social Issues / Self-Esteem & Self-Reliance; Bilderbuch